1
You visited us 1 times! Enjoying our articles? Unlock Full Access!
Question

# Solve: 2(3u - v) = 5uv 2(u + 3v) = 5uv

A
u = 2, v = 1
Right on! Give the BNAT exam to get a 100% scholarship for BYJUS courses
B
u = 3, v = 2
No worries! We‘ve got your back. Try BYJU‘S free classes today!
C
u = 4, v = 3
No worries! We‘ve got your back. Try BYJU‘S free classes today!
D
Insufficient data
No worries! We‘ve got your back. Try BYJU‘S free classes today!
E
None of the above
No worries! We‘ve got your back. Try BYJU‘S free classes today!
Open in App
Solution

## The correct option is A u = 2, v = 12(3u−v)=5uv⇒6v−2u=5 2(u+3v)=5uv⇒2v+6u=5 Putting 1v=x and 1u=y, we get 6x−2y=5……(1) 2x+6y=−2……(2) Multiplying Equation (1), and Equation (2) by 3 and 1 respectively, we have 18x−6y=15 and 2x+6y=5 Adding these two equations, we get 20x=20, i.e., x=1 From Equation (1), y=(6x−52)=(6×1−52)=12 ∴u=1y=2 and v=1x=1

Suggest Corrections
6
Join BYJU'S Learning Program
Related Videos
Cramer's Rule
MATHEMATICS
Watch in App
Join BYJU'S Learning Program